Leutik Asal Nirilik: Budaya, Nilai, dan Makna Kerja di Perkebunan Teh Bandung Selatan - Aulia, Shofia Az Zahra; Herawati, Erna; Sita, Kralawi (Universitas Padjadjaran, 2023)
Tea plantations have contributed essentially to the Indonesia economy. It also provides jobs for people living surrounding the plantation; although the wages are limited. Despite the low wage, however, working in the tea plantation has become the backbone for the household income of the tea pickers. This research aims to explore and describe views and opinions of tea plantation workers in southern highland Bandung about their job and how it means to them. It also explores how workers develop work culture and ethic and how they perceive it in contrast to core values of the tea plantation company. The daily living of the workers were explored to reveal local Sundanese cultural values that might underpin their work culture and ethic. Using a qualitative method with an ethnographic model, this research collected primary data through participant observation and in-depth interviews with tea plantation workers. The research findings suggest that tea plantation workers apply the concept of leutik asal nirilik (little but continuously); which refers to their income. This concept is rooted in the local Sundanese values of acceptance and perseverance; and this motivated them to keep up the job despite some possibilities to access other jobs. Workers view their job as meaningful despite the low wages and have a sense of belonging to the job. However, they do have some aspirations and visions about their career and welfare. They have a work culture and ethic which are in line with the core values of the tea plantation company, named AKHLAK, which has been introduced to them only recently.